Variation in plastic consumption: social group size enhances individual susceptibility to an evolutionary trap. (October 2022) - Pollack, L.; Munson, A.; Zepeda, E.; Culshaw-Maurer, M.; Sih, A.
Abstract : Anthropogenic change forces animals to navigate novel conditions, including evolutionary traps formed by decoupling cues from their previously evolved meaning. One underexplored feature that could drive variation in response to traps is social context. We looked at how group size influences the behaviour of western mosquitofish, Gambusia affinis, group members, including eating novel foods. Individuals in larger groups were faster to recover after experiencing a predator cue and faster to feed on known food items. Moreover, fish in larger groups were more likely to try novel foods, including microplastics, a common evolutionary trap. We also found evidence of a group level behavioural syndrome, in which a consistent proportion of individuals performed a behaviour across assays (i.e. resumed general activity following a predator cue, ate known food and ate novel food). Our results provide evidence that group size can influence the severity of an evolutionary trap and that, regardless of group size, group identity can have a strong effect on individual behaviour. Highlights: We examined group size effects on mosquitofish behaviour across multiple contexts. Fish in larger groups recovered more quickly following a predator cue. Fish in larger groups began eating familiar food faster. Fish in larger groups were more likely to try novel foods, including microplastics. Group identity was also a strong predictor of individual behaviour.